Analisis Waktu Kerja untuk Menentukan Jumlah Tenaga Kerja dalam Pemenuhan Permintaan di UD.ABC - Fachril Aliffiansyah; Sajiyo, Sajiyo (SURYA TEKNIKA, 2024)
ABC is a small and medium industry that produces various kinds of shovels. The products produced by UD.ABC are wooden-handled shovels and iron shovels. Every day UD.ABC targets to produce 65 and 45 dozen wooden-handled shovels and iron shovels. But the production target could not be met. One way that targets cannot be met is influenced by the performance and consistency of each operator, therefore it is necessary to determine the standard time for each operator in order to maximize consistency in completion. After calculating the standard time, the standard time for OP1 was 33.25 seconds, OP2.3 14.19 seconds, OP4 33.47 seconds, OP5 23 seconds, OP6 26.59 seconds, OP7.8 29.1 seconds. And additional workers are needed to meet production targets. The additional workforce was carried out at OP4 by 1 person,and OP6 by 1 person.